Analisis Semiotika Representasi Budaya dan Isu Sosial dalam Film Animasi The Journey : Studi Kasus Nilai-Nilai Perjuangan - Zulfan Bintang Bagas Kara; Hafidz Hafidz (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The animated film The Journey is the result of a collaboration between Japan and Saudi Arabia which raises the theme of Islamic history, especially the struggle of the people of Mecca in defending the Kaaba from attacks by Abraha troops. This research aims to analyze the representation of culture and social issues in the film using a semiotic approach. This study examines how this film depicts the combination of Arab and Japanese culture and conveys the values ​​of the struggle through symbols, indices and icons in its visual narrative. The research results show that this film represents Arab culture through costumes, historical settings and strong Islamic values, while its visual and cinematic elements reflect the influence of Japanese animation. Apart from that, the social issues in this film highlight aspects of Islamic preaching, including the values ​​of aqidah, shari’ah and morals which are displayed in the struggle of the main character, Aws Bin Jubair. The values ​​of struggle depicted in this film include courage, sacrifice, unity and faith which are the main pillars in facing great challenges. Thus, the film The Journey not only functions as entertainment but also as a medium for preaching and education that can provide insight into Islamic history and inspire the values ​​of struggle in modern life.